The Future of Music Copyright Collectives in the Digital Streaming Age - Priest, Eric (The Columbia Journal of Law & the Arts, 2021)
Copyright collectives are critical to the economic health of the music industry, but they are at a curious crossroads. Collective copyright management is used more extensively in the music business than ever before. Expanded collective copyright management for digital streaming is the centerpiece of the Music Modernization Act (MMA)—the most extensive revision to the Copyright Act in two decades. At the same time, major music publishers, who rely heavily on collective licensing revenue, are on a years-long mission to end collective licensing for certain digital streaming rights. These trends reflect changes that streaming technology has caused in music consumption, distribution, and revenue generation. Digital streaming has emerged as the dominant music consumption model, accounting for eighty-three percent of music revenues in the United States in 2020. This rapid rise to dominance naturally has profound implications for the future of music licensing. The licensing needs of streaming service providers are unprecedented in scale. Spotify, for example, currently hosts over 70 million recordings, with more than 60,000 new recordings uploaded every day. Most of these recordings encompass two copyrighted works that must be licensed separately: a copyrighted sound recording and a copyrighted underlying musical composition. Streaming services’ need for such a massive number of licenses highlights the value of collectives that enable streaming services to interface with a manageable number of licensors. It also highlights the importance of blanket licenses that permit spontaneous use of millions of works relatively free from infringement liability. At the same time, the importance of collective licensing to copyright owners has decreased in the streaming age. Streaming is a highly concentrated market: Spotify, Apple Music, and Amazon Music together control two-thirds of the global streaming market. Thus, it has never been easier for copyright owners to license a handful of platforms that deliver the lion’s share of revenue. Further, technology has markedly reduced the costs of use-tracking and royalty distribution. All streams are automatically logged, and royalties are automatically distributed based on usage data. As a result, the major record labels often directly license millions of sound recordings to streaming services without using a collective. Historically, collective copyright management has been valuable for both copyright owners and users of copyrighted works. The primary advantage is reduced transaction costs. Across the globe, there are millions of music copyright owners and millions of businesses that use copyrighted works. In some cases, individual transactions for large numbers of works would be prohibitively costly for both sides. Collective copyright management creates a one-stop shop for licensors and licensees, drastically reducing transaction costs. Collective copyright management further benefits copyright owners by sharing and thereby reducing administrative and enforcement costs. It further benefits users by reducing potential liability for frequent and spontaneous uses, especially through blanket licensing that empowers licensees to make unlimited use of all works in a licensor’s catalog. The major concern with collective licensing has long been the monopoly pricing potential of collective copyright control, especially when collective licensing is combined with blanket licensing. If one entity holds the rights to license the majority of popular songs, it can exact monopoly rents from anyone seeking to use music. Radio stations, streaming services, nightclubs, and other music-centric businesses would have no latitude to seek alternatives if the rights to license the music they need were concentrated in one entity. Music licensing, therefore, has long been a heavily regulated market, controlled through a combination of compulsory licensing regimes, statutory limitations and exceptions to exclusive copyright rights, and competition authority oversight. The question is whether such heavy regulation is necessary going forward—or, more to the point, whether collective licensing is necessary going forward. Collective licensing has dominated the music public performance rights market for a century. The two major performance rights organizations (PROs)—American Society of Composers, Authors and Publishers (ASCAP) and Broadcast Music, Inc. (BMI)—offer blanket licenses for millions of works, albeit under strict regulation by the Department of Justice (DOJ) to deter market power abuses. But this model increasingly seems like a vestige of the analog age. Today, there is a relative handful of high-value licensees operating globally. Streaming services have the technological infrastructure to work with a huge number of licensors, unlike the radio stations and nightclubs of yore. Because technology enables nearly frictionless virtual licensing and automated usage tracking and royalty distribution, a plethora of music rights and royalty administration businesses have flourished that are capable of administering direct public performance rights licensing and royalty collection on copyright holders’ behalf. The performance licensing that still involves high transaction costs—licensing of radio stations and brick-and-mortar businesses such as stores, fitness studios, and bars—accounts for less than fifteen percent of PRO revenues. Further, as I discuss in Part IV.B, licensing even in those arenas is vulnerable to disruption. The upshot is that music publishers, especially major publishers, are eager to eschew collective licensing in the digital streaming space so they can negotiate higher direct-licensing fees for streaming. As I discuss in Part III.C.3, publishers’ plans have been derailed for the time being by DOJ consent decrees that prohibit PROs from selectively licensing members’ works. Many licensees, on the other hand, are generally satisfied with how collective licensing currently functions in the performance rights space. The two major PROs are so heavily regulated that their blanket license offerings are comparable to compulsory licenses: The PROs’ pricing and licensing discretion is substantially curtailed under rate court and DOJ oversight. Meanwhile, competition from a new PRO (which poaches some of the legacy PROs’ most valuable catalog) and from a burgeoning music rights administration industry adds further pressure, casting doubt on the long-term viability of the legacy PROs. If the legacy PROs deteriorate and publishers seek direct licenses for performance rights, will licensees lobby for a blanket compulsory performance rights license? There is precedent for such a compulsory license, as a new compulsory blanket licensing regime came into effect in 2021, mandated by the MMA, for a related right: the right to make and distribute phonorecords of nondramatic musical works, including by means of “digital phonorecord delivery.” In essence, this is a compulsory license for the right to digitally deliver—via download or stream—a copyrighted song encompassed in a sound recording. The MMA also created a new collective—the Mechanical Licensing Collective (MLC) (so-called because the compulsory license covers what was traditionally called the “mechanical right,” or the right to reproduce musical works in formats used for mechanical playback)—to administer the compulsory license. The MMA comes two decades after the creation of another compulsory right prompted by digital streaming: the compulsory right available to “noninteractive” digital music services (essentially, internet radio webcasters and satellite radio broadcasters) to transmit sound recordings. A bespoke licensing collective, SoundExchange, was created to administer that compulsory license as well. In total, the licensing landscape for the U.S. digital music streaming sector involves six collectives: the MLC, SoundExchange, and four PROs. The only licenses in the streaming landscape not administered by licensing collectives are licenses for the use of sound recordings by “interactive” streaming services, such as Apple Music and Spotify. These direct licenses also happen to be by far the most lucrative licenses in the music business. The two compulsory streaming licenses of relatively recent vintage (and their respective collectives) seem entrenched for the foreseeable future. However, uncertainty surrounds the future of streaming performance royalties. Will major publishers seek to direct-license streaming performances and withdraw their rights from PROs? Will they seek instead to phase out streaming performance royalties in favor of a single, all-encompassing musical composition royalty stream managed by the MLC? Or will they maintain the status quo: music composition streaming royalties split into performance and mechanical royalties administered and distributed by five or more different collectives. In the long term, the third possibility seems the least likely due to the inefficiencies and lack of flexibility in the current structure. The other possibilities would not be costless, however, as bypassing the PROs for streaming royalties would markedly weaken—if not ruin—the PROs on which publishers would still rely for non-streaming performance royalties. In this Article, I examine the present state of collective copyright management and collective licensing in the United States and identify the factors likely to determine the future of collective copyright management due to new usage tracking technology and the rise of digital streaming. In Part I, I lay the terminological groundwork for subsequent discussion by defining and distinguishing the related concepts of collective licensing, direct licensing, compulsory licensing, blanket licensing, and collective copyright management. In Part II, I lay the necessary doctrinal groundwork for later discussion by disentangling the complex lattice of rules concerning digital music rights that are subject to collective management in the United States. This Part then discusses the rise of the new blanket compulsory mechanical license under the MMA and puts it into the historical context of compulsory licenses arising in response to rapid technological shifts in delivery models for copyrighted works. In Part III, I discuss the role of the PROs, the areas in which they add value as well as their shortcomings, and the pressures they face in the digital streaming arena due to a confluence of heavy regulation, increased competition, and technological changes that reduce the need for collective licensing. In Part IV, I consider the future of collective licensing in the digital streaming age, in particular the future of the MLC and the PROs.